WHO Growth Charts for Diagnosis of Malnutrition - Phadke, Mrudula; Menon, Pramila; Giri, Purushottam; Bodhankar, Uday; Prabhu, Sanjay; Kinjawadekar, Upendra (Indian Journal of Community Health, 2023)
Child malnutrition is a major public health issue worldwide. An estimated 144 million children under age 5 are stunted, 47 million are wasted and 38.3 million have overweight or obesity. Around 45% of deaths among children under 5 years of age are linked to undernutrition.1 Measuring the growth of infants and children is an important part of child health surveillance and gives an idea about the nutritional status of the baby. Inadequate infant growth leads to under-nutrition in children in many low- and middle-income countries, which, if followed later in life by an increased intake of calories, can result in overweight or obesity and non- communicable diseases.